Species of the genus Helicotylenchus Steiner, 1945 from an indigenous forest in Rwanda, with description of Helicotylenchus wilmae sp. n. (Nemata: Hoplolaimidae) (Journal of Nematode Morphology and Systematics, 2012)
Five species, one new and four known, belonging to the genus Helicotylenchus were found in samples taken in an indigenous tropical forest at the foot of Mount Sabyinyo, Volcanoes National Park, northern Rwanda: H californicus Sher, 1966, H. dihystera (Cobb, 1893) Sher, 1961, H. nitens Siddiqi, 1995 and H. variocaudatus (Luc, 1960) Fortuner, 1984 and H. wilmae sp. n. The new species is characterised by its body 500-675 μm long in females and 520 μm in males, stylet 25-29 μm long in females, lip region with 10 or 11 annuli, presence of fasciculi, V = 57-61, presence of males, gubernaculum with an incurved proximal end, and tail symmetrical with annulated projection. H. californicus and H. nitens are new records for Rwanda and this is the fi rst report of H. nitens outside its type locality in Cameroon.